RELEVANSI TAFSIR AYAT-AYAT TARBAWI TERHADAP PENDIDIKAN ISLAM KONTEMPORER - Selvy Yuspitasari (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study examines the relevance of the tarbawi (educational) interpretation of Qur’anic verses to contemporary Islamic education. The tarbawi exegesis provides guidance for developing a holistic, integrative education that emphasizes character building and spiritual awareness. This research analyzes how the principles embedded in the Qur’an can be applied in a modern context, including the development of physical, intellectual, and spiritual aspects, as well as the integration of knowledge with moral and religious values. The findings indicate that understanding tarbawi interpretation serves not only as a normative foundation but also as a strategic reference for curriculum design, teaching methods and educational evaluation. Therefore, the tarbawi exegesis plays a crucial role in creating relevant, adaptive and effective Islamic education that fosters the comprehensive development of human beings.